PENERAPAN METODE WATERFALL PADA PERANCANGAN APLIKASI SISTEM PELAYANAN ADMINISTRASI PENDUDUK BERBASIS WEB (Studi Kasus: Kantor Kelurahan Jatimulya Kota Depok) - Lulu Nailufar (2023)
The Jatimulya Sub-district Office located in Cilodong District, Depok City, has not fully optimized information technology in their public service system. All services for residents can only be done directly at the Jatimulya Sub-district Office since the services offered are still done manually and not computerized, which means that residents must come directly to the office. This makes it difficult for residents to obtain services. In the process of creating documents, officers still use manual methods, such as Microsoft Office. The management of incoming application letters and resident data is also still done manually through bookkeeping or archiving methods. Thus, manual work can lead to the risk of human error or mistakes in creating documents, the loss of incoming application letters and resident data, as well as damaged archives due to the sheer volume of documents. The purpose of this study is to create a web-based application system for administrative services to simplify the process for residents. Data collection methods used for this study include observation and interviews, and the system analysis method used is PIECES. The Waterfall design method was used for system design, and the Black Box Testing method was used for system testing, with MySQL as the database. The result of this study is a web-based administrative service system application that makes it easier for residents to apply for documents online and helps sub-district office employees create documents, manage incoming application letters, and resident data accurately. This application system can provide optimal service to residents.